Research Priorities on One Health: A Bibliometric Analysis - Miao, Liyuan; Li, Hao; Ding, Wei; Lu, Shenning; Pan, Shuning; Guo, Xiaokui; Zhou, XiaoNong; Wang, Duoquan (Frontiers in public health, 2022)
One Health is an emerging research area that has received increasing attention globally. In this study, we aimed to explore the global research trend and hotspots of One Health and provide a reference for potential future research and practices.ObjectiveOne Health is an emerging research area that has received increasing attention globally. In this study, we aimed to explore the global research trend and hotspots of One Health and provide a reference for potential future research and practices.This was a bibliometric descriptive study of publications on One Health in four directions, including zoonotic diseases, antimicrobial resistance, food safety, and vector-borne infections. Publications from 2003 to 2021 were retrieved using the Scopus database on One Health, which were screened based on the PRISMA guidelines. Keywords were analyzed and visualized using VOSviewer software.MethodsThis was a bibliometric descriptive study of publications on One Health in four directions, including zoonotic diseases, antimicrobial resistance, food safety, and vector-borne infections. Publications from 2003 to 2021 were retrieved using the Scopus database on One Health, which were screened based on the PRISMA guidelines. Keywords were analyzed and visualized using VOSviewer software.A total of 12,815 publications were included. The annual number of publications and those on each topic showed a gradual increase from 181 in 2003 to 1,647 in 2020, with an average annual growth rate of about 20.2%; the top three countries in terms of the number of publications were the United States of America (n=3,588), the United Kingdom (n=1,429) and China (n=1,233); the major research subjects were mainly in the natural sciences, with fewer social sciences subjects involved (n = 312; 1%). The main research directions within the area of zoonotic diseases included viral, bacterial, parasitic zoonotic diseases, and vector-borne diseases, with a small amount of antimicrobial resistance research. The major research interests within antimicrobial resistance were Enterobacteriaceae drug-resistant bacteria, methicillin-resistant Staphylococcus aureus, Pseudomonas aeruginosa, and antimicrobial resistance gene detection; research on food safety clustered around agronomy research, aquaculture research as well as a small amount of antimicrobial resistance research in food; and research on vector-borne diseases focused on mosquito-borne infectious diseases, tick-borne infectious diseases, and vectors.ResultsA total of 12,815 publications were included. The annual number of publications and those on each topic showed a gradual increase from 181 in 2003 to 1,647 in 2020, with an average annual growth rate of about 20.2%; the top three countries in terms of the number of publications were the United States of America (n=3,588), the United Kingdom (n=1,429) and China (n=1,233); the major research subjects were mainly in the natural sciences, with fewer social sciences subjects involved (n = 312; 1%). The main research directions within the area of zoonotic diseases included viral, bacterial, parasitic zoonotic diseases, and vector-borne diseases, with a small amount of antimicrobial resistance research. The major research interests within antimicrobial resistance were Enterobacteriaceae drug-resistant bacteria, methicillin-resistant Staphylococcus aureus, Pseudomonas aeruginosa, and antimicrobial resistance gene detection; research on food safety clustered around agronomy research, aquaculture research as well as a small amount of antimicrobial resistance research in food; and research on vector-borne diseases focused on mosquito-borne infectious diseases, tick-borne infectious diseases, and vectors.The scientific literature on One Health has witnessed a rising global trend. Most research has focused on the human-animal health interface, while environmental health is often neglected. Research subjects mainly fall within natural science disciplines, with less social science research. More support needs to be given to interdisciplinary and intersectoral cooperation and research in the future.ConclusionsThe scientific literature on One Health has witnessed a rising global trend. Most research has focused on the human-animal health interface, while environmental health is often neglected. Research subjects mainly fall within natural science disciplines, with less social science research. More support needs to be given to interdisciplinary and intersectoral cooperation and research in the future.